Respiratory virus concentrations in human excretions that contribute to wastewater: a systematic review and meta-analysis - Sarah A. Lowry; Marlene K. Wolfe; Alexandria B. Boehm (IWA Publishing, 2023)
Concentrations of nucleic acids from a range of respiratory viruses in wastewater solids collected from wastewater treatment plants correlate to clinical data on disease occurrence in the community contributing to the wastewater. Viral nucleic acids enter wastewater from excretions deposited in toilets or drains. To relate measured concentrations in wastewater at a treatment plant to the number of community infections, viral nucleic-acid concentrations in human excretions are needed as inputs to a mass balance model. Here, we carried out a systematic review and meta-analysis to characterize the concentrations and presence of influenza A and B, respiratory syncytial virus, metapneumovirus, parainfluenza virus, rhinovirus, and seasonal coronaviruses in stool, urine, mucus, sputum, and saliva. We identified 220 data sets from 50 articles and reported viral concentrations and presence in these excretions. Data were unevenly distributed across virus type (with the most available for influenza) and excretion type (with the most available for respiratory excretions). Most articles only reported the presence or absence of the virus in a cross-sectional study design. There is a need for more concentration data, including longitudinal data, across all respiratory virus and excretion types. Such data would allow quantitatively linking virus wastewater concentrations to numbers of infected individuals. HIGHLIGHTS Concentrations of respiratory viruses in excretions are necessary to translate measured concentrations in wastewater to infections in a community.; This systematic review collates information on the concentration and presence of a range of respiratory viruses in human excretions.; Data availability varies by virus type and excretion type.;